Construction and development of an Asian family scale: the path and importance of the effort - Musa, Ramli (Malaysian Journal of Psychiatry, 2013)
The escalation in the aspect of social ills especially among Malaysian teenagers in the recent decade has evoked our interest in the need to look at the family dynamic. High prevalence of drug abuse, conduct misacts,truancy, teenage pregnancy and promiscuous behaviour, is the main indicator on the need to conduct family studies.